Synthesis Optimization of Activated Carbon Driven from Scrap Tire for Adsorbent Yield and Methylene Blue Removal under Response Surface Methodology - Estifanos Kassahun; Solomon Tibebu; Yobsen Tadesse; Nigist Awish (Advances in Materials Science and Engineering)
This study aimed to investigate the synthesis optimization of activated carbon-driven scrap tires for adsorbent yield and methylene blue removal under response surface methodology. The scrap tire sample was activated by KOH using ethanol as a solvent. The optimized activated carbon was characterized using proximate analysis, scanning electron microscope (SEM), X-ray diffraction (XRD), and Brunauer Emmett Teller (BET) method. The activated carbon was demineralized using 5 M NaOH +  98% H2SO4 (1 : 1) as a solvent to enhance the surface area. Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich models were used to check the adsorption isotherm. The adsorption kinetics was checked using pseudo-first-order and pseudo-second-order models. Weber-Morris intraparticle diffusion model was used to study the diffusion mechanism. The optimum impregnation ratio, impregnation time, and carbonization temperature for synthesizing the activated carbon were 2 g/g, 12 hr, and 700°C, respectively. The moisture content, volatile matter, ash content, fixed carbon, and bulk density of the activated carbon were 6.13%, 9.42%, 5.34%, 79.11%, and 0.89 mg/L, respectively. The surface area of optimized activated carbon was enhanced by demineralization process and increased from 53 m2/g to 260.26 m2/g. Temkin adsorption isotherm with R2 values of 0.982 and pseudo-second-order adsorption kinetics with R2 values of 0.999 best fits the experimental data respectively. Intraparticle diffusion was not the only rate-controlling step for both optimized and demineralized (NaOH + H2SO4) activated carbon. It can be concluded that the optimized and demineralized activated carbon derived from scrap tires has a promising potential to be used as a low-cost adsorbent in developing countries including Ethiopia. However, further investigation needs to be conducted before scaling up at industrial level.